Daily sodium consumption and CVD mortality in the general population: systematic review and meta-analysis of prospective studies. Issue 4 (22nd May 2014) - Poggio, Rosana; Gutierrez, Laura; Matta, María G; Elorriaga, Natalia; Irazola, Vilma; Rubinstein, Adolfo
Abstract Objective The purpose of the present study was to determine whether elevated dietary Na intake could be associated with CVD mortality. Design We performed a systematic review and meta-analysis of prospective studies representing the general population. The adjusted relative risks and their 95 % confidence intervals were pooled by the inverse variance method using random-effects models. Heterogeneity, publication bias, subgroup and meta-regression analyses were performed. Settings MEDLINE (since 1973), Embase (since 1975), the Cochrane Library (since 1976), ISI Web of Science, Google Scholar (until September 2013) and secondary referencing were searched for inclusion in the study. Subject Eleven prospective studies with 229 785 participants and average follow-up period of 13·37 years (range 5·5–19 years). Results Higher Na intake was significantly associated with higher CVD mortality (relative risk=1·12; 95 % CI 1·06, 1·19). In the sensitivity analysis, the exclusion of studies with important relative weights did not significantly affect the results (relative risk=1·08; 95 % CI 1·01, 1·15). The meta-regression analysis showed that for every increase of 10 mmol/d in Na intake, CVD mortality increased significantly by 1 % (P=0·016). Age, hypertensive status and length of follow-up were also associated with increased CVD mortality. Conclusions Higher Na intake was associated with higher CVD mortality in the general population; this result suggests a reduction in Na intake to prevent CVD mortality from any cause.